Single-Frequency PPP-RTK: Theory and Experimental Results - Odijk, Dennis; Teunissen, Peter; Khodabandeh, A. (Springer, 2014)
Integer ambiguity resolution enabled Precise (cm-level) Point Positioning (PPP) is feasible if corrections from a GPS network of CORS stations are applied to the single-receiver phase and code data of a user. The concept of PPP-RTK requires a proper definition and quality of the PPP-user network corrections, which are satellite clocks, satellite phase biases and ionospheric delays interpolated to the approximate location of the user. The availability of the satellite phase bias corrections enables the user to carry out integer resolution of ambiguities that are double-differenced, i.e., relative to those of the pivot receiver in the network. The availability of the interpolated ionospheric corrections is not absolutely required, however PPP-RTK for single-frequency users would virtually be impossible without them. A proper handling of the network corrections implies that the PPP-user should take their uncertainty into account as well. In order to limit the amount of information to be transmitted to the user, in this contribution we provide a closed-form analytical expression for the variance matrix of the network corrections which a single-frequency user can apply in his processing. Experimental results of single-frequency PPP-RTK for both a high-grade geodetic receiver as well as a low-grade mass-market receiver demonstrate that although single-epoch integer ambiguity resolution is not possible, single-frequency ambiguity resolution enabled cm-level PPP is feasible based on an accumulation of less than 10 min of observations plus network corrections on average.